Breathing frequency patterns during submaximal and maximal front crawl swim with and without respiratory valve - Strumbelj, B.; Kapus, J.; Usaj, A.; Kapus, V. (Kinesiology, 2007)
The purpose of the present study was to ascertain the effect of a respiratory valve (RV) and tubes during three different swimming tests (submaximal and maximal 200m front crawl swim and front crawl swimming to exhaustion) on a breathing frequency, selected biomechanical parameters such as stroke rate and number of breaths, and parameters of blood acid-base status and blood lactate concentration. Twelve former competitive male swimmers performed each swimming test twice: first, with an RV, and second, without an RV. Swimming with an RV induced a slower maximal 200m front crawl swim and shorter front crawl swimming to exhaustion in comparison with swimming without an RV. Furthermore, patterns of the breathing frequency during the submaximal and maximal swimming tests also differed between swimming with an RV and swimming without an RV. Significant differences of [LA-] after maximal 200m front crawl swimming between swimming with an RV and swimming without an RV (p=0.05) were found. Significant differences in [LA-] and [HCO3-] after swimming to exhaustion between swimming with an RV and swim-ming without an RV (p=0.01 and p=0.05, respectively) were also found. Therefore, it may be concluded that when an RV is used for measuring respiratory parameters during swimming, a different pattern of breathing (comparing to swimming without an RV) may occur.